The Significance and Integration of Religious Moderation in Student Organizations on Religious Campuses - Rahmatiah, Rahmatiah; Suhendra Arbani, Tri; Rais Asmar, Abd; Umar, Kusnadi; Chaerul Risal, M; Fajri, Muhammad (KnE Social Sciences, 2022)
Data from the Ministry of Religion show that many well-known universities and religious colleges are exposed to radicalism. This is closely related to student organizations as a forum for students to gather and gain understanding outside of the lecture room. This paper aimed to examine the basic concepts and views of student organizations in filtering radicalism and liberalism with a religious moderation approach. This study used qualitative research methods with a phenomenological approach to consider the scope of student organizations, both internal and external, at UIN Alauddin Makassar. The level of students’ understanding of radicalism was explored along with the integration of the basic views of religious moderation in a campus organization. Moderation has become a filter tool for radicalism in the campus environment. Keywords: significance, organization, religious moderation